Electronic content management systems use and implementation in highly integrated businesses - Izza Arshad, N. (2013)
Many organizations have invested large amounts of money in implementing Electronic Content Management Systems (ECMS), which refers to the technologies used to manage, store and deliver business-related information across the organization. However, research indicates that many ECMS implementations fail to yield the kind of information sharing that is useful for business process executions. From the IS literature point of view, this is not because of the technologies, but it is due to ways ECMS is implemented and used which is not aligned with organization's way of doing business. Therefore, this paper explores how organizations that emphasize high integration and low standardization of business processes termed as Coordination use and implement ECMS to support its business operations. We suggest guidelines that explain the ways ECMS should be used and implemented in Coordination organizations that include (1) ways to use ECMS for sharing business process-related information, (2) ECMS infrastructure, (3) ways to manage content and (4) administration of ECMS. These findings are grounded in the analysis of qualitative data from one case study. The finding is significant for business and IT managers because it will guide them with ways to use ECMS and gain more benefits from these types of systems. Â© IDOSI Publications, 2013.